Mathematical relationships of models of two-phase flows in channels of reactors and steam generators of NPP's for the calculation of their hydrodynamic characteristics - Yefimov, О.V.; Pylypenko, M.M.; Kavertsev, V.L.; Harkusha, T.A.; Yesypenko, T.O. (Вопросы атомной науки и техники, 2022)
Two-phase flows of the working substance in the steam-generating channels of reactors of single-circuit NPP’s and steam generators of two- and three-circuit NPP’s represent the joint movement of liquid (feed water) and steam in the form of a steam-water mixture. The forms of movement of two-phase flows are much more diverse, and the laws of their movement are much more complicated than flows of single-phase media, and they are characterized by a large number of parameters. This is due to the fact that when the flow of the steam-water mixture moves in the steam-generating channels, mass exchange processes occur between the liquid and vapor phases of the mixture, in which the volumes of the phases change; the interfaces between the phases of the mixture vary along the length of the channel and often do not have a distinct character. The cross-sectional mean velocities of the liquid and vapor phases of the flow are not equal to each other, and the difference in the velocities of the phases in the steady-state mode of motion of the two-phase flow depends on the mass flow rate of the steam-water mixture, its pressure, direction of flow, heating intensity, and other indicators. All this complicates experimental studies and calculations of parameters and hydrodynamic (gas-dynamic) characteristics of two-phase flows of a steam-water mixture of a working substance in reactors and steam generators of nuclear power plants. The article discusses mathematical relationships for calculating the hydraulic characteristics of two-phase flows of different structures during the movement of a steam-water mixture in the steam-generating channels of reactors and steam generators of nuclear power plants, namely bubble, slug, rod, dispersed. The ratios are given for various designs of the channels of reactors and steam generators. Двофазні потоки робочої речовини в парогенеруючих каналах реакторів одноконтурних АЕС і парогенераторів дво- і триконтурних АЕС являють собою сумісний рух рідини (живильної води) і пари у вигляді пароводяної суміші. Форми руху двофазних потоків значно різноманітніші, а закони їх руху істотно складніші, ніж потоків однофазних середовищ і характеризуються вони великою кількістю параметрів. Це обумовлено тим, що при русі потоку пароводяної суміші в парогенеруючих каналах відбуваються процеси масообміну між рідкою і паровою фазами суміші, при яких змінюються об'єми фаз; межі розділу між фазами суміші змінюються по довжині каналу і часто не мають чітко вираженого характеру. Середні по перерізу швидкості рідкої і парової фаз потоку не рівні між собою, причому відмінність в швидкостях фаз при сталому режимі руху двофазного потоку залежить від масової витрати пароводяної суміші, її тиску, напряму руху потоку, інтенсивності нагріву і інших чинників. Все це ускладнює експериментальні дослідження і розрахунки параметрів і гідродинамічних (газодинамічних) характеристик двофазних потоків пароводяної суміші робочої речовини в реакторах і парогенераторах АЕС. У статті розглянуті математичні співвідношення для розрахунку гідравлічних характеристик двофазних потоків різної структури при русі пароводяної суміші в парогенеруючих каналах реакторів і парогенераторів АЕС, зокрема бульбашкового, снарядного, стрижневого, дисперсного. Співвідношення наведені для різного конструктивного виконання каналів реакторів і парогенераторів. Двухфазные потоки рабочего вещества в парогенерирующих каналах реакторов одноконтурных АЭС и парогенераторов двух- и трехконтурных АЭС представляют собой совместное движение жидкости (питательной воды) и пара в виде пароводяной смеси. Формы движения двухфазных потоков значительно разнообразнее, а законы их движения гораздо сложнее, чем потоков однофазных сред, и характеризуются они большим количеством параметров. Это обусловлено тем, что при движении потока пароводяной смеси в парогенерирующих каналах происходят массообменные процессы между жидкой и паровой фазами смеси, при которых изменяются объемы фаз; границы раздела между фазами смеси меняются по длине канала и часто не имеют четко выраженного характера. Средние по сечению скорости жидкой и паровой фаз потока не равны между собой, причем отличие в скоростях фаз при установившемся режиме движения двухфазного потока зависит от массового расхода пароводяной смеси, ее давления, направления движения потока, интенсивности нагрева и других показателей. Все это затрудняет экспериментальные исследования и расчеты параметров и гидродинамических (газодинамических) характеристик двухфазных потоков пароводяной смеси рабочего вещества в реакторах и парогенераторах АЭС. В статье рассмотрены математические соотношения для расчета гидравлических характеристик двухфазных потоков разной структуры при движении пароводяной смеси в парогенерирующих каналах реакторов и парогенераторов АЭС, а именно пузырькового, снарядного, стержневого, дисперсного. Соотношения приведены для различного конструктивного исполнения каналов реакторов и парогенераторов.